2012
DOI: 10.1093/hmg/dds273
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic, genomic and translational approaches identify CRMP1 for a role in schizophrenia and its underlying traits

Abstract: Schizophrenia is a chronic illness of heterogenous biological origin. We hypothesized that, similar to chronic progressive brain conditions, persistent functional disturbances of neurons would result in disturbed proteostasis in the brains of schizophrenia patients, leading to increased abundance of specific misfolded, insoluble proteins. Identification of such proteins would facilitate the elucidation of molecular processes underlying these devastating conditions. We therefore generated antibodies against poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 74 publications
9
72
0
Order By: Relevance
“…Such links between DISC1 and reelin have been hypothesised previously (Deutsch et al, 2010;Bader et al, 2012), and the two proteins share several common pathway elements, which are known to include LIS1, GSK3β, Akt and APP (Assadi et al, 2003;Ohkubo et al, 2003;Brandon et al, 2004;Hashimoto et al, 2006;Jossin and Goffinet, 2007;Hoe et al, 2009;Mao et al, 2009;Young-Pearse et al, 2010). Our results, however show, for the first time a direct functional link between DISC1 and reelin, with DISC1 found to alter the post-translational regulation of reelin by proteolytic cleavage.…”
Section: Introductionsupporting
confidence: 76%
“…Such links between DISC1 and reelin have been hypothesised previously (Deutsch et al, 2010;Bader et al, 2012), and the two proteins share several common pathway elements, which are known to include LIS1, GSK3β, Akt and APP (Assadi et al, 2003;Ohkubo et al, 2003;Brandon et al, 2004;Hashimoto et al, 2006;Jossin and Goffinet, 2007;Hoe et al, 2009;Mao et al, 2009;Young-Pearse et al, 2010). Our results, however show, for the first time a direct functional link between DISC1 and reelin, with DISC1 found to alter the post-translational regulation of reelin by proteolytic cleavage.…”
Section: Introductionsupporting
confidence: 76%
“…Recent studies of gene copy number variants and exome sequencing of single-nucleotide polymorphisms (SNPs) implicate genes modulating cytoskeleton proteins, NMDA receptors and VGCCs, converging on pathways regulating synaptic plasticity. 55 It is not surprising that CRMP1, also called dihydropyriminidase-like 1 (DPYSL1), which interacts with reelin and DISC1, 18 and CRMP2 (DPYSL2), which affects not only neurites but also neurotransmitter release and modulates Ca 2+ fluxes through activation of NMDA receptors, 28 have been included in the list of schizophrenia susceptibility genes. CRMP1 was identified as altered protein in a search for schizophreniaspecific epitopes from patients' post-mortem brain fractions.…”
Section: Human Nervous System Diseases: Insights From Crmp-altered Lementioning
confidence: 99%
“…Another gene, CRMP1 (collapsin response mediator protein 1), which is dependent on DISC1, is also related to anhedonia. In this multidisciplinary study, it was shown that in lymphoblastoid cell lines of schizophrenia patients there was an increase in CRMP1 expression, suggesting a potential role of a bloodbased diagnostic marker [91]. Another DISC1-related gene was downregulated in CSF of schizophrenia patients, namely CCDC3 (coiledcoil domain-containing protein 3 precursor) [58].…”
Section: Cytoskeletal Alterationsmentioning
confidence: 87%
“…Besides, animal models of DISC1-related diseases displayed anhedonia-like behavior, indicated by immobility in the forced swimming test. Impairment of this gene has been related to disrupted axonal transport in neurons [91]. Another gene, CRMP1 (collapsin response mediator protein 1), which is dependent on DISC1, is also related to anhedonia.…”
Section: Cytoskeletal Alterationsmentioning
confidence: 99%